Is there a competition between endemic pink pigeon (Nesoenas mayeri) and invasive Madagascar turtle-dove (Nesoenas picturata) in lowland Mauritius? - Eiselt, Claire (2014)
Mauritius, one of the Mascarene islands in the Indian Ocean, was identified as a biodiversityhotspot by IUCN and as an Important Bird Area by BirdLife International, mostly because ofits endemic species richness. Habitat destruction and introductions of many alien invasivespecies already caused extinctions and reduction of populations to critical low levels. Theendemic pink pigeon (Nesoenas mayeri), one of Mauritius emblematic species, has recoveredfrom less than 20 birds in the mid 1970s to 343 free-living individuals in 2014 among whichthe subpopulation established on Ile aux Aigrettes, a Nature Reserve offshore islet. This studyinvestigated if pink pigeons were competing with exotic Madagascar turtle-dove (Nesoenaspicturata), a sister species widespread on the island, for food and nesting sites. There productive success of both species was also investigated by nests monitoring. Significant differences in the diet, foraging behaviour and nesting preferences of pink pigeon and Madagascar turtle-dove were found on Ile aux Aigrettes. Pink pigeon was predominantlyeating leaves and favouring areas of mature canopy forest, preferring tall ebony trees Diospyros egrettarum for nesting. Madagascar turtle-dove was mostly a fruit eater and wasnesting at lower levels, with no big preference in the plant species choice, and in open areas orforest edges. Proportion of successful nests was 3 times higher for the exotic N.picturata. Differing ecological requirements indicate that divergence between these congeners may besufficient for them to coexist and exploit contrasting resources on this restored islet. Nevertheless, we discuss the implications of such coexistence in relation to pathogenTrichomonas gallinae transmission which can affect pink pigeon long-term recovery programme.